Is social media the top priority for seeking and sharing information about COVID-19 among Indonesian students? - Azahar Kasim; Reza Safitri; Isma Adila; Arif Budi Prasetya; Nufian Febriani; Wayan Weda Asmara Dewi; Ahmad Muwafik Saleh; Moch Fauzie Said (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study evaluates whether social media plays a role as the main source of information and, at the same time, as information sharing. Research on information-seeking behaviour, information needs, and information sharing has received increasing attention from various scientific communities since COVID-19 was declared a global epidemic. However, efforts have not been made to compare the capabilities of digital and interpersonal channels in both aspects of seeking and sharing information in Indonesia. Among the siege of information sources, identifying the primary sources of information used by students is important if the government is to intervene in health policies to overcome the pandemic. With an online survey conducted on 624 students, this study revealed that social media, which appears to be dominant as a source of COVID-19 information, cannot influence the behaviour of sharing information with others. The ETA correlation test confirms no correlation between the information source and information sharing behaviour. Indonesian students are moved to pass on information from interpersonal communication. In the two-stage communication model, individuals obtain information from the media and then discuss the information with others, which emerged in the conventional era and is still valid in today's digital era. The issue of trust is still inherent in social media, which makes it difficult to confirm the information on social media to be shared with others. The study explains that although communication technology has developed into the digital era, it does not necessarily eliminate the role of conventional technology.